Newly Diagnosed Colonic Adenocarcinoma: The Presenting Sign in a Young Woman with Undiagnosed Crohn’s Disease in the Absence of Primary Sclerosing Cholangitis and a Normal Microsatellite Instability Profile - Brett Matthew Lowenthal; Ann M. Ponsford Tipps (Case Reports in Pathology)
Ulcerative colitis has long been linked with an increased risk for colonic adenocarcinoma, whereas Crohn’s disease (CD) has recently been reported to pose a similar increased risk. We report a 33-year-old healthy female with no family history who presented with abdominal pain and a colon mass. Histopathology revealed a moderately differentiated adenocarcinoma extending through the muscularis propria with metastatic lymph nodes and intact mismatch repair proteins by immunohistochemical expression and gene sequencing. The nonneoplastic grossly uninvolved background mucosa showed marked crypt distortion, crypt abscesses, CD-like lymphoid hyperplasia, transmural inflammation, and reactive epithelial atypia. Additional patient questioning revealed frequent loose stools since she was a teenager leading to diagnosis of a previously undiagnosed CD without primary sclerosing cholangitis (PSC). The adenocarcinoma is suspected to be related to the underlying CD. Newly diagnosed adenocarcinoma in a young female as the presenting sign for CD in the absence of PSC is extremely rare.